Role of agricultural diversification in mitigating income risk in Eastern India - VENKATESH, P; KURIACHEN, PHILIP; SEN, BISWAJIT; JHA, GIRISH K; SINGH, D R; M, BALASUBRAMANIAN; SANGEETHA, V (The Indian Journal of Agricultural Sciences, 2021)
The study attempts to verify the role of agricultural diversification as a mechanism of coping with income risk. For this purpose, the study estimates the level of agricultural diversification across the eastern Indian states sourcing secondary data on value of output for the period spanning from 1999-00 to 2013-14. Further, income risk at state level also measured through a comprehensive and comparable risk index. It was observed that in eastern Indian states, Chhattisgarh had highest level of risk and Bihar had lowest risk level. Further, factors which can positively influence level of agricultural diversification were segregated and it was observed that, fertilizer usage, percentage of irrigated area, cropping intensity, market access and farm sizes had direct impact on level of diversification for overall agriculture and in cereals, pulses and oilseeds sub-sectors, though in varying degrees. The study also established that level of agricultural diversification reduces risk level while land fragmentation increases risk level.